Developing a comprehensive action plan for excellent service quality delivery in Malaysian Polytechnic / Azrin Jalasi, Hady Fairuz Salsidu and Nur Izany Mohamad - Jalasi, Azrin; Salsidu, Hady Fairuz; Mohamad, Nur Izany (2014)
As a Technical Education and Vocational Training ( TVET ) institution, polytechnic plays a vital role in developing the socio-economic of the nation. After more than 45 years of operation, Malaysian polytechnic has produced more than 350,000 semi-professionals workforce and middle executives in various industries outside and inside of Malaysia. However, despite the importance of polytechnic in the nation development, empirical research on service quality in Malaysian polytechnic sector has been limited. Recently, the number of new students enrolled in the Malaysian polytechnic has decreased rapidly and the service quality performance was suspected as the main cause of this problem. Therefore, this study aims to identify specific service quality dimensions for polytechnic, to assess the relationship between service quality and customer's satisfaction in polytechnic, to determine the effect of service quality towards customers' satisfaction in polytechnic and lastly but not least to propose a comprehensive action plan for an excellent service quality delivery in Malaysian polytechnic. A sample of 388 students in Malaysian polytechnic has participated in this research. In this study, it has been confirmed that service quality dimensions namely non-academic aspects, academic aspects, reputation, accessibility and program issues have a significant and positive relationship with the student's satisfaction in Malaysian polytechnic.